Zinc-Dependent Modulation of α2- and α3-Glycine Receptor Subunits by Ethanol - McCracken, Lindsay M. (Alcohol Clin Exp Res, 2013)
BACKGROUND: Strychnine-sensitive glycine receptors (GlyRs) are expressed throughout the brain and spinal cord and are among the strongly supported protein targets of alcohol. This is based largely on studies of the α1-subunit; however, α2- and α3-GlyR subunits are as or more abundantly expressed than α1-GlyRs in multiple forebrain brain areas considered to be important for alcohol-related behaviors, and uniquely some α3-GlyRs undergo RNA editing. Nanomolar and low micromolar concentrations of zinc ions potentiate GlyR function, and in addition to zinc’s effects on glycine-activated currents, we have recently shown that physiological concentrations of zinc also enhance the magnitude of ethanol (EtOH)’s effects on α1-GlyRs. METHODS: Using 2-electrode voltage-clamp electrophysiology in oocytes expressing either α2- or α3-GlyRs, we first tested the hypothesis that the effects of EtOH on α2- and α3-GlyRs would be zinc dependent, as we have previously reported for α1-GlyRs. Next, we constructed an α3P185L-mutant GlyR to test whether RNA-edited and unedited GlyRs contain differences in EtOH sensitivity. Last, we built a homology model of the α3-GlyR subunit. RESULTS: The effects of EtOH (20 to 200 mM) on both subunits were greater in the presence than in the absence of 500 nM added zinc. The α3P185L-mutation that corresponds to RNA editing increased sensitivity to glycine and decreased sensitivity to EtOH. CONCLUSIONS: Our findings provide further evidence that zinc is important for determining the magnitude of EtOH’s effects at GlyRs and suggest that by better understanding zinc/EtOH interactions at GlyRs, we may better understand the sites and mechanisms of EtOH action.